(untitled) (Eurasian Research Bulletin, 2023)
This article delves into the transformative role of simulation training within the Intensive Care Unit (ICU), exploring its multifaceted impact on the competence of healthcare professionals. The immersive power of realistic replication, team collaboration, and honed decision-making skills emerges as a cornerstone in preparing professionals for the high-stakes environment of critical care. Risk-free learning unfolds as a sanctuary where errors become catalysts for mastery, and skill diversity is cultivated through scenarios ranging from routine tasks to high-acuity events. The symphony of simulation harmonizes not just technical skills but team dynamics, fostering confidence that resonates beyond the simulation lab.